Knowing history in schools : powerful knowledge and the powers of knowledge (Knowledge and the curriculum., 2021)
Knowing History in Schools explores how we can best understand knowledge-building in history education and aims to navigate the challenges that knowledge-building processes pose for learning history in schools.